Kapitalismus versus Marktwirtschaft: Karl Marx und Fernand Braudel - Faber, Malte; Petersen, Thomas (Discussion paper series, 2018)
Since the beginning of the finance crisis, the notion of capitalism and the adjective capitalistic are more and more employed in public discourse without making an attempt to define it. In contrast, the concept of market economy is less used. We try in this paper to differentiate both concepts by going back to the approaches by Karl Marx (1818-1883) and Fernand Braudel (1902-1985). Marx does not use the term capitalism but only capitalistic production, while Braudel argues on the basis of a wealth of empirical evidence that one has to differentiate between capitalism and market economy, because he sees a contrast between them. For this reason, he has different view of a capitalistic economy as Marx has.
Keywords: Graue Literatur